2016
DOI: 10.14814/phy2.12736
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous caveolin-3 mice show increased susceptibility to palmitate-induced insulin resistance

Abstract: Insulin resistance and diabetes are comorbidities of obesity and affect one in 10 adults in the United States. Despite the high prevalence, the mechanisms of cardiac insulin resistance in obesity are still unclear. We test the hypothesis that the insulin receptor localizes to caveolae and is regulated through binding to caveolin‐3 (CAV3). We further test whether haploinsufficiency for CAV3 increases the susceptibility to high‐fat‐induced insulin resistance. We used in vivo and in vitro studies to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 42 publications
(62 reference statements)
2
20
0
Order By: Relevance
“…It can induce IR in liver cells, skeletal muscles and cardiomyocytes, and plays an important role in the formation of diseases such as atherosclerosis and diabetes. [25][26][27] In this study, PA levels in GDM and PE patients showed an upward trend, and GDM were more prominent than PE patients. PA inhibits insulin-stimulated cellular glucose transport and increases blood glucose levels by attenuating tyrosine phosphorylation of the insulin receptor substrate and inhibiting the activation of phosphoinositide 3-kinase, which blocks insulin signaling.…”
Section: Fatty Acidssupporting
confidence: 48%
“…It can induce IR in liver cells, skeletal muscles and cardiomyocytes, and plays an important role in the formation of diseases such as atherosclerosis and diabetes. [25][26][27] In this study, PA levels in GDM and PE patients showed an upward trend, and GDM were more prominent than PE patients. PA inhibits insulin-stimulated cellular glucose transport and increases blood glucose levels by attenuating tyrosine phosphorylation of the insulin receptor substrate and inhibiting the activation of phosphoinositide 3-kinase, which blocks insulin signaling.…”
Section: Fatty Acidssupporting
confidence: 48%
“…In humans, partial gene deficiencies in multiple loci, rather than complete loss of function of a given gene, underlie complex diseases such as obesity and Type 2 diabetes (22). Other studies examining the effects of heterozygosity on glucose and lipid metabolism have underscored the additional insights gained from mouse models of partial gene deficiency that are relevant to human disease variants (1,17,42). Therefore, our results highlight the value of examining the consequences of partial gene deficiency in preclinical animal models of complex diseases, as these data will provide a basis to help interpret and evaluate functional consequences of reduced gene expression due to polymorphisms or epigenetic changes in the gene regulatory regions uncovered by large-scale genome-wide studies in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography was performed with a Vevo2100 (VisualSonics), 40 MHz solid-state transducer, and the papillary muscle was used as orientation for the acquisition of short-axis M-mode images. Data were analyzed by the heart function package provided by VisualSonics Systems [10]. Diastolic and systolic LV internal dimensions were measured to evaluate LV structural changes.…”
Section: Cardiac Ultrasoundmentioning
confidence: 99%